Supply chain management of Abul Khair Steel Products Ltd. (Flat Steel) - Islam, Chowdhury Md. Tarek Bin (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.